ZFP64:NCOA3 gene fusion defines a novel subset of spindle cell rhabdomyosarcoma. Issue 11 (20th May 2022) - Han, Rachel; Dermawan, Josephine K.; Demicco, Elizabeth G.; Ferguson, Peter C.; Griffin, Anthony M.; Swanson, David; Antonescu, Cristina R.; Dickson, Brendan C.
Abstract: Spindle cell rhabdomyosarcoma represents a rare neoplasm characterized by monomorphic spindle cells with a fascicular architecture and variable skeletal muscle differentiation. Following incidental identification of a ZFP64::NCOA3 gene fusion in an unclassified spindle cell sarcoma resembling adult‐type fibrosarcoma, we performed a retrospective archival review and identified four additional cases with a similar histology and identical gene fusion. All tumors arose in adult males (28–71 years). The neoplasms were found in the deep soft tissues, two were gluteal, and one each arose in the thigh, abdominal wall, and chest wall. Morphologically, the tumors were characterized by spindle cells with a distinctive herringbone pattern and variable collagenous to myxoid stroma. The nuclei were relatively monomorphic with variable mitotic activity. Three tumors had immunoreactivity for MyoD1, and four contained variable expression of desmin and smooth muscle actin. All cases tested for myogenin, CD34, S100, pankeratin, and epithelial membrane antigen were negative. Targeted RNA sequencing revealed a ZFP64::NCOA3 fusion product in all five tumors. Three patients developed distant metastases, and two ultimately succumbed to their disease within 2 years of initial diagnosis. This study suggests ZFP64::NCOA3 fusions define a novel subtype of rhabdomyosarcoma with a spindle cell morphology and aggressive clinical behavior. The potential for morphologic and immunohistochemical overlap with several other sarcoma types underscores the value of molecular testing as a diagnostic adjunct to ensure accurate classification and management of these neoplasms.